2019
DOI: 10.1111/jocd.12895
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of bioactive compounds isolated from cordyceps and their protective effects against UVB‐irradiated HaCaT cells

Abstract: Summary Background Excessive free radicals, generated from the metabolic reaction in organisms, have been implicated in many human diseases as well as aging process. Nowadays, many synthetic substances have been developed as anti‐oxidation cosmetic ingredients. However, man‐made antioxidants often have certain toxicity and side effects, which make their application under strict control. Therefore, more and more researchers focus on natural antioxidants because of their advantages. Aims In this study, CE obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A large number of studies have reported that natural plant polysaccharides have a good biological protective effect on skin photoaging damage. For example, after HaCaT cells were treated with UVB irradiation (30 mJ/cm 2 ), the addition of Cordyceps polysaccharide was shown to increase the activity of SOD and reduce the content of MDA in the cells, which has a notable effect on antioxidation and free radical scavenging in vitro [ 50 ]. In addition, Wang et al studied the UV protection of seaweed sulfated polysaccharides (HFPS) in HaCaT cells and in zebrafish in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have reported that natural plant polysaccharides have a good biological protective effect on skin photoaging damage. For example, after HaCaT cells were treated with UVB irradiation (30 mJ/cm 2 ), the addition of Cordyceps polysaccharide was shown to increase the activity of SOD and reduce the content of MDA in the cells, which has a notable effect on antioxidation and free radical scavenging in vitro [ 50 ]. In addition, Wang et al studied the UV protection of seaweed sulfated polysaccharides (HFPS) in HaCaT cells and in zebrafish in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The superoxide anion (O 2 ·− ) scavenging activity of the GS and fermentation samples was assayed using the method described by Tang et al [ 69 ], with slight modifications. For this, 2.25 mL of Tris-HCl buffer (50 mM, pH 8.2), 0.1 mL of sample, and 0.2 mL of catechol solution (3 mM, pre-warmed at 37 °C before use) were mixed.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that Cordyceps consists of various chemical constituents, such as nucleosides, lipids, saccharides, mannitol, and amino acids [22]. Modern research has shown that Cordyceps possesses many bioactive functions, such as anti-tumor [23], anti-inflammatory [24], antioxidation [25] and immunomodulation [26] activities. However, its anti-cancer composition is unclear.…”
Section: Introductionmentioning
confidence: 99%